RNA m6A methylation across the transcriptome - Sendinc, Erdem; Shi, Yang (Molecular cell, 2023)
Since the early days of foundational studies of nucleic acids, many chemical moieties have been discovered to decorate RNA and DNA in diverse organisms. In mammalian cells, one of these chemical modifications, N6-methyl adenosine (m6A), is unique in a way that it is highly abundant not only on RNA polymerase II (RNAPII) transcribed, protein-coding transcripts but also on non-coding RNAs, such as ribosomal RNAs and snRNAs, mediated by distinct, evolutionarily conserved enzymes. Here, we review RNA m6A modification in the light of the recent appreciation of nuclear roles for m6A in regulating chromatin states and gene expression, as well as the recent discoveries of the evolutionarily conserved methyltransferases, which catalyze methylation of adenosine on diverse sets of RNAs. Considering that the substrates of these enzymes are involved in many important biological processes, this modification warrants further research to understand the molecular mechanisms and functions of m6A in health and disease.